IS THE FLOWER OF PULASAN (NEPHELIUM RAMBOUTAN-AKE) A PROTOGYNY OR PROTANDRY? - Nina Ratna Djuita; Alex Hartana; Tatik Chikmawati; Dorly Dorly (Floribunda, 2021)
Pulasan is an androdioecious plant that has both male and hermaphrodite flowers on separate plants. The objectives of this study were to obtain data about the anatomical structure of pulasan flower and to investigate whether the pistil and the stamens of pulasan flower reach maturity at different times. The anatomical observation was done on compound flowers taken from three male trees and three hermaphrodite trees. Two compound flowers that still in buds, about to bloom and fully bloom were picked from each tree.  Flowers were observed in a cross and longitudinal section. The results showed that the sepals of pulasan flower comprised of the uniseriate epidermis and multilayered polyhedral parenchymal cells. Stamen development started from the anther followed by the formation of the filament. The pollen of hermaphrodite pulasan flowers reached maturation earlier than the pistil. The pistil development started from the expansion of meristem cells in the center of the flower and ends with the warp of the stigma.